A novel serum metabolomic panel distinguishes IgG4‐related sclerosing cholangitis from primary sclerosing cholangitis. (21st February 2022) - Radford‐Smith, Daniel E.; Selvaraj, Emmanuel A.; Peters, Rory; Orrell, Michael; Bolon, Jonathan; Anthony, Daniel C.; Pavlides, Michael; Lynch, Kate; Geremia, Alessandra; Bailey, Adam; Culver, Emma L.; Probert, Fay
Abstract: Background & Aims: Primary sclerosing cholangitis (PSC) and IgG4‐related sclerosing cholangitis (IgG4‐SC) are chronic fibro‐inflammatory immune‐mediated hepatobiliary conditions that are challenging to distinguish in a clinical setting. Accurate non‐invasive biomarkers for discriminating PSC and IgG4‐SC are important to ensure a correct diagnosis, prompt therapy and adequate cancer surveillance. Methods: We performed nuclear magnetic resonance (NMR)‐based metabolomic profiling using serum samples collected prospectively from patients with PSC ( n = 100), IgG4‐SC ( n = 23) and healthy controls (HC; n = 16). Results: Multivariate analysis of the serum metabolome discriminated PSC from IgG4‐SC with greater accuracy (AUC 0.95 [95%CI 0.90–0.98]) than IgG4 titre (AUC 0.87 [95%CI 0.79–0.94]). When inflammatory bowel disease (IBD) was excluded as a comorbid condition (IgG4‐SC n = 20, PSC n = 22), the diagnostic AUC increased to 1.0, suggesting that the metabolome differences identified are not a result of the increased prevalence of IBD in PSC relative to IgG4‐SC patients. Serum lactate ( p < .0001), glucose ( p < .01) and glutamine ( p < .01) metabolites were increased in IgG4‐related disease (IgG4‐RD) and IgG4‐SC individuals compared to PSC, whereas mobile choline ( p < .05), 3‐hydroxybutyric acid ( p < .01) and ‐CH3 lipoprotein resonances ( p < .01) were decreased. Conclusions: Taken together, serum metabolomic profiling has the potential to be incorporated as a diagnostic criterion, independent of IgG4 titre, to improve the diagnosis of IgG4‐RD and help distinguish IgG4‐SC from PSC.